The contribution of management to economic growth: a review. (1st September 2014) - Glaister, Keith W.
Abstract : A review of the literature indicates that the contribution of management to economic growth has been largely obscured in theory and ignored in empirical work. In contrast, the place of the entrepreneur in the process of growth is well recognised and widely accepted. The main goal of this paper is to develop an argument for the place of management in the process of growth, and to maintain that in the modern free market economy management's role is at least as important as that of the entrepreneur Routine innovation in established firms is emphasised as a fundamental, normal part of management activity, and as such highlights the importance of management for economic growth. However, management is not homogeneous and the actions of managers differentially affect the performance outcomes of firms. Hence the quality of management, and the adoption of appropriate management practices, matters and directly impacts economic growth. In recognising that management makes a significant contribution, both in terms of ensuring efficiency in the use of factor inputs and effectiveness in terms of driving incremental innovation, new research is necessary at the firm level in order to develop this understanding.